Anterior versus posterior fusion surgery in idiopathic scoliosis: A comparison of health-related quality of life and radiographic outcomes in Lenke 5C curves - results from the Swedish spine registry. (October 2021) - Charalampidis, Anastasios; Möller, Hans; Gerdhem, Paul
Abstract: Purpose: To compare health-related quality of life and radiographic outcomes in patients treated with either anterior or posterior fusion surgery for Lenke 5C type idiopathic scoliosis. Methods: We used data from the Swedish spine registry and identified 59 patients with idiopathic scoliosis treated with fusion for Lenke 5C type curves; 27 patients underwent anterior surgery and 32 underwent posterior surgery. All patients had pre- and postoperative radiographic data and postoperative clinical data at a minimum of two years after surgery. Patient-reported outcomes measures included the Scoliosis Research Society (SRS)-22r, EuroQoL 5 dimensions 3 levels (EQ-5D-3L), EQ-visual analogue scale (VAS) and VAS for back pain. Radiographic assessment included measurement of the angle of the major curve, disc angulation below the lowest instrumented vertebra, curve flexibility, rate of curve correction, differences in sagittal parameters, number of fused vertebrae and length of fusion. Results: The mean age at surgery was 16 years in both groups. The mean follow-up time was 3.8 years. There were no significant differences in the SRS-22r score and EQ-5D-3L index at follow-up (all p ≥ 0.2). Postoperatively, both the anterior and posterior fusion group demonstrated a significant correction of the major curve (p ≤ 0.001) with no significant difference of the correction rate between the groups (p = 0.4). The posterior fusion group had shorter operative time (p < 0.001) and higher perioperative blood loss (p = 0.004) while the anterior group had lower number of fused vertebrae (p< 0.001). Conclusion: The type of surgical approach for Lenke 5C curves is not associated with differences in health-related quality of life, despite the lower number of fused vertebrae after anterior surgery. Level of Evidence: III